Analisis Pengaruh Ayunan Elektroda Las Terhadap Uji Kekerasan Baja Aisi 1045 Pada Area Haz - Agus, Darma Afriliansyah; Tuparjono, Tuparjono; Erwansyah, Erwansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
In the welding process, the swing of the electrode is very influential on the mechanical properties of the weld. The purpose of this study was to determine the hardness value in the HAZ area of ​​AISI 1045 steel due to differences in SMAW welding electrode swing. The method in this study uses experimental research methods, namely describing comparisons of treated specimens using the help of the Microsoft Excel application. The material used in this study was AISI 1045 medium carbon steel which was welded using SMAW welding with variations of zig-zag, circular and C swing electrodes with 1G position. The results of this study prove that the electrode swing has a significant effect on the hardness value. It can be seen that the test material with a circular swing pattern has a higher value than the zigzag and C swing patterns. This is shown by testing the hardness test in the HAZ area where the circular swing pattern gets average. -the highest average hardness value is 23.47 HRC. Meanwhile, the lowest average hardness value is in the C swing pattern of 20.46 HRC. Electrode swing has an influence on the hardness value. The circular swing pattern has a higher value than the zigzag and C swing patterns.